STRATEGIC DEVELOPMENT OF WIDYAISWARA SOFT SKILLS ROOTED IN QUR’ANIC TEACHINGS AT JAKARTA’S RELIGIOUS TRAINING CENTER - Ghozi, Ali; Saihu, Made; Hariyadi, M.; Hotimah, Husnul (Balai Diklat Keagamaan Jakarta, 2025)
This research departs from the need to develop the competence of widyaiswara, which has emphasised hard skills, while the soft skills aspect has not received adequate attention. The Qur'an provides a clear foundation for the development of soft skills in the form of praiseworthy qualities or morals that must be owned and continuously developed. These characters include consistency (istiqomah), humility (tawadhu'), sincerity, integrity, and an attitude of iḥsān (doing good). This competency is intended for widyaiswara to develop a stable, wise, mature, and authoritative character and to serve as a role model for students. This research uses a descriptive qualitative method with a library research approach. The data sources are taken from verses of the Qur'an related to the development of soft skills, supported by interpretations from various books of interpretation, spanning styles, periods, and schools of thought. This study concludes that the strategy of developing widyaiswara soft skill competencies according to the Qur'an can be realised through tadzkirah (reminder), uswah ḥasanah (exemplary) and ihsan. Tadzkirah is done through routine recitation or discussion of Qur'anic values; uswah ḥasanah is implemented through good example or noble character; ihsan is realised through good behaviour in social and professional interactions. This research emphasises that soft skills are the primary foundation that strengthens hard skills, in line with the views of classical scholars and modern research, which states that the mastery of strong soft skills largely determines professional success.